Cybersecurity as a Requirement of Constitutional Security: A Study on State Guarantees in the Modern State - Saad Jassim Al-Zamly, Assist. Lect. Hussam (Basra studies journal, 2026)
This research addresses the relationship between cybersecurity and constitutional security in light of the rapid digital transformation taking place in modern states, accompanied by a significant increase in cyber threats and crimes targeting individuals, institutions, and critical state infrastructure. The study aims to clarify the conceptual framework of both cybersecurity and constitutional security, analyze their interrelationship and integration, and highlight the safeguards adopted by the state to achieve what may be termed “constitutional cybersecurity.” The research adopts a descriptive-analytical approach through the examination of relevant legal concepts. It concludes that achieving cybersecurity is not limited to technical aspects alone, but requires a comprehensive legal and legislative framework, specialized institutions, and effective safeguards that strike a balance between security requirements and the protection of rights and freedoms. The study also emphasizes the importance of international cooperation in combating transnational cybercrime, as well as the necessity of continuously updating national legislation to keep pace with rapid technological developments.